The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/land10010085
|View full text |Cite
|
Sign up to set email alerts
|

Urban Green Space Composition and Configuration in Functional Land Use Areas in Addis Ababa, Ethiopia, and Their Relationship with Urban Form

Abstract: This study aimed to assess the compositions and configurations of the urban green spaces (UGS) in urban functional land use areas in Addis Ababa, Ethiopia. The UGS data were extracted from Landsat 8 (OLI/TIRS) imagery and examined along with ancillary data. The results showed that the high-density mixed residence, medium-density mixed residence, and low-density mixed residence areas contained 16.7%, 8.7%, and 42.6% of the UGS, respectively, and together occupied 67.5% of the total UGS in the study area. Manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…We found that landscape configurational heterogeneity is associated with perception. In a decision-making context in which stakeholders would like to increase landscape heterogeneity for improving perception, particular attention must be paid to the impacts on landscape composition, another important structuring element of UGS [61]. The importance of balancing configuration and compositional elements is a key ecological concern to promote biodiversity [29], particularly in UGS, and thus visitor well-being [62].…”
Section: Discussionmentioning
confidence: 99%
“…We found that landscape configurational heterogeneity is associated with perception. In a decision-making context in which stakeholders would like to increase landscape heterogeneity for improving perception, particular attention must be paid to the impacts on landscape composition, another important structuring element of UGS [61]. The importance of balancing configuration and compositional elements is a key ecological concern to promote biodiversity [29], particularly in UGS, and thus visitor well-being [62].…”
Section: Discussionmentioning
confidence: 99%
“…5d). Likewise a study by Woldesemayat and Genovese (2021) a rmed that inner parts of the urban centers in developing countries have low supply of UGS, which increases towards the peripheries.…”
Section: Urban Green Space Availabilitymentioning
confidence: 97%
“…Urban green space (UGS) refers to part of urban land covered with vegetation (Rahimi, 2020), and is recognized solution for creating smart and resident friendly urban centers (Tan et al, 2013;Demuzere et al, 2014;Wolch et al, 2014;Jennings et al, 2016;Daniels et al, 2018;Woldesemayat and Genovese, 2021). UGS has multitude of social, economic, ecological, and planning bene ts (Attwell, 2000;Kaczynski and Henderson, 2008;Baycan-Levent and Nijkamp, 2009;Sadeghian and Vardanyan, 2013;Kabisch et al, 2016;Pulighe et al, 2016;Anguluri and Narayanan, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that a well-developed and managed urban green infrastructure contributes significantly to urban sustainability by providing significant benefits in the areas of social, economic, and environmental concerns [20,73,74]. In both developed and developing countries, urban green infrastructure can provide passive and active recreation and help to meet a community's leisure needs by providing places for playing, sport, recreation, special events, and other leisure activities [75,76].…”
Section: Related Workmentioning
confidence: 99%